Application of numerical modeling to reservoir immersion assessment and control in dual-formation hydrogeological unit - Yun Yang (IWA Publishing, 2021)
Reservoir immersion is a serious environmental geological issue in a dual-formation structural reservoir bank (DFB) induced by dynamic surface water impoundment (SWI) that has implications for low-lying farmland and buried infrastructure. It is a major challenge to identify the dynamic immersion process and make economic and scientific joint mitigation measures for controlling groundwater immersion. Here, we develop a three-dimensional groundwater flow model and apply it to evaluate and control reservoir immersion in the typical low-lying DFB of Xingan Navigation and Power Junction Project (XGNPJ) across Ganjiang River in Jiangxi Province, China. The field-scale model is well calibrated to predict where the groundwater immersion could potentially occur. Furthermore, the effectiveness of the countermeasures adopted for the reduction of reservoir immersion areas were analysed based on the simulation model by considering the projected future combination scenarios of engineering measures. Results indicate that without engineering mitigation measures, SWI generates groundwater inundation across 23% of the total study area. Comprehensive comparative analysis on different seepage control schemes reveals that the joint engineering measures can effectively control the immersion range to 5% of the total area. The findings can provide scientific basis for groundwater immersion assessment and guide immersion control of XGNPJ project. HIGHLIGHTS Hydrological analysis related to the groundwater-surface water interactions.; Impacts of groundwater depth on reservior immersion.; Establishing a FEFLOW model for regional groundwater assessment and identification of the dynamic immersion process.; Implementation of model assessment for controlling groundwater immersion.; The joint engineering measures can effectively control the immersion range.;